T cell Ca2+ microdomains through the lens of computational modeling - Gil Montoya, Diana C.; Ornelas-Guevara, Roberto; Diercks, Björn-Philipp; Guse, Andreas H.; Dupont, Geneviève (Frontiers in Immunology, 2023)
Cellular Ca 2+ signaling is highly organized in time and space. Locally restricted and short-lived regions of Ca 2+ increase, called Ca 2+ microdomains, constitute building blocks that are differentially arranged to create cellular Ca 2+ signatures controlling physiological responses. Here, we focus on Ca 2+ microdomains occurring in restricted cytosolic spaces between the plasma membrane and the endoplasmic reticulum, called endoplasmic reticulum-plasma membrane junctions. In T cells, these microdomains have been finely characterized. Enough quantitative data are thus available to develop detailed computational models of junctional Ca 2+ dynamics. Simulations are able to predict the characteristics of Ca 2+ increases at the level of single channels and in junctions of different spatial configurations, in response to various signaling molecules. Thanks to the synergy between experimental observations and computational modeling, a unified description of the molecular mechanisms that create Ca 2+ microdomains in the first seconds of T cell stimulation is emerging.